The Effect of Computerized Adaptive Testing on Motivation and Anxiety: A Systematic Review and Meta-Analysis. (July 2023) - Akhtar, Hanif; Silfiasari,; Vekety, Boglarka; Kovacs, Kristof
Although many studies have been carried out on the psychometric aspects of computerized adaptive testing (CAT), its psychological aspects are less researched. Early studies claimed that CAT can be more motivating and induce less anxiety than traditional fixed-item tests (FIT). The purpose of this systematic review and meta-analysis was to gain a comprehensive understanding of the effects of CAT on motivation and anxiety in comparison to traditional fixed-item testing. Seven databases were examined. Articles were eligible if they employed an empirical study containing a direct comparison between CAT and FIT. Meta-analytical results showed no overall effect of test type on anxiety and motivation when comparing CAT with FIT ( k = 11, g+ = 0.06, p = .28). However, easier CAT had positive effect compared with FIT ( k = 2, g+ = .22, p < .001). Certain modifications in CAT administration can provide positive psychological effects for test-takers.